The Complementary Nature of Fundamental and Technical Analysis: Evidence from Indonesia - Waworuntu, Stephanus Remond; Suryanto, Hendra (International Research Journal of Business Studies, 2010)
Fundamental analysis and technical analysis has been used independently to predict the stock price movement. Both type of analysis usually used without interacting each other. This study was intended to test the complementary nature of fundamental and technical analysis as to whether it will increase the explanatory power to explain the stock price movement in Indonesia LQ45 market. The result shows that fundamental or technical analysis alone in isolation have the ability to predict future prices. But, by integrating both factors together in a single model will give the superior explanatory power to the prediction. However, in Indonesia stock market, technical analysis plays the biggest role in determining future price movements, while technical data was widely available in the market rather than the fundamental data such as analyst’s forecasted EPS. These findings prove that fundamental analysis can be used in determining which stocks or portfolio is prosperous in the future, and technical analysis can be used in determining the right time to buy or sell the stocks. By integrating both type of analysis, investors could have superior profit than the buy and hold strategy. The result should also enrich the knowledge of stock traders in gaining more profit.